2015
DOI: 10.1371/journal.pone.0132059
|View full text |Cite
|
Sign up to set email alerts
|

High-Dose α-Tocopherol Supplementation Does Not Induce Bone Loss in Normal Rats

Abstract: Oxidative stress affects bone turnover. Preventative effects of antioxidants such as vitamin E on reduced bone mineral density and fractures associated with aging, osteoporosis, and smoking have been examined in animals and humans. The effects of vitamin E (α-tocopherol; αT) on bone health have yielded conflicting and inconclusive results from animal studies. In this study, to determine the bone effects of αT, we investigated the in vivo effects of αT on the bone mineral density, bone mass, bone microstructure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 35 publications
0
11
0
1
Order By: Relevance
“…Vitamin E supplements are widely consumed at the rate of ~ 250 mg/day, while the recommended daily dose is around ~ 150 mg/day. While the supplement intake is justifiable by its beneficial effects, recent reports on the role of vitamin E in bone functions have raised serious concerns due to its effect on bone homeostasis [13,[35][36][37]. Recently, Fujita et al [13] utilized mouse genetics and showed that vitamin E could promote osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…Vitamin E supplements are widely consumed at the rate of ~ 250 mg/day, while the recommended daily dose is around ~ 150 mg/day. While the supplement intake is justifiable by its beneficial effects, recent reports on the role of vitamin E in bone functions have raised serious concerns due to its effect on bone homeostasis [13,[35][36][37]. Recently, Fujita et al [13] utilized mouse genetics and showed that vitamin E could promote osteoclast formation.…”
Section: Discussionmentioning
confidence: 99%
“…APTT, activated partial thromboplastin time; MK-4, menaquinone-4; PK, phylloquinone; ucOC, uncarboxylated osteocalcin. young female rats (11), or male mice and ovariectomized female mice fed a high-fat diet (12). In the present study, we used young male rats as the experimental animal, following the report of Fujita et al The PK and RRR-a-tocopherol contents in the control diet were at 0.75 mg/kg and 50 mg/kg, respectively, in accordance with the AIN93 rodent diet (15).…”
Section: Discussionmentioning
confidence: 92%
“…Recently, Fujita et al reported that excess intake of a-tocopherol reduced bone mass in rats and mice (9). After that, other researchers also examined the effect of excess a-tocopherol on the bone mass of rats and mice, but no reduction of bone mass was confirmed (10)(11)(12). The reason for these contradictory results is still unknown.…”
mentioning
confidence: 99%
“…De acuerdo con los resultados del presente trabajo, Kasai et al (2015) evaluaron los efectos de la Vitamina E en los huesos en ratas normales alimentados con dietas que contenían diferentes niveles de a-Tocoferol, encontrando una tendencia a un aumento de la masa ósea dominante en la osteogénesis en el hueso esponjoso vertebral secundario, en el que se produce la remodelación ósea activa en los animales tratados con esta vitamina.…”
Section: Discussionunclassified